Pengaruh Promosi Kesehatan terhadap Pengetahuan dan Sikap Kader Posyandu tentang Kusta - Suryanda, Suryanda; Iryani, Lepi; Rustati, Nelly (FORIKES, 2023)
Posyandu cadres are also expected to have good knowledge about leprosy so that they can play an active role in reducing stigmatization. This study aims to determine the effect of health promotion through lectures, leaflets and movie show on the knowledge and attitudes of posyandu cadres about leprosy in Prabumulih City. The research design was non-randomized pretest-posttest with a control group. The research sample was 54 active posyandu cadres in Prabumulih city and divided into 2 groups. The first group was given health promotion using the lecture and leaflet method; while the second group was given lecture methods and movie show. In the phases before and after the intervention in both groups knowledge and attitudes were measured using a questionnaire. The test for differences in knowledge and attitudes between the two groups was carried out using the t test. The results of the analysis of the differences between the pre- and post-treatment phases showed a p-value of 0.000, both for the group with the lecture and moview show interventions; so it was interpreted that both methods can increase knowledge and attitudes significantly. Furthermore, it was concluded that the lecture method combined with leaflets and movie show was effective in increasing knowledge and building a positive attitude of health cadres about leprosy.Keywords: leprosy; posyandu cadres; knowledge; attitude; movie show ABSTRAK Kader posyandu juga diharapkan memiliki pengetahuan yang baik tentang kusta sehingga dapat berperan aktif dalam mengurangi stigmatisasi. Penelitian ini bertujuan untuk mengetahui pengaruh promosi kesehatan dengan ceramah, leaflet dan pemutaran film terhadap pengetahuan dan sikap kader posyandu tentang kusta di Kota Prabumulih. Desain penelitian ini adalah non randomized pretest-posttest with control group. Sampel penelitian adalah 54 kader posyandu aktif di kota Prabumulih dan dibagi menjadi 2 kelompok. Pada fase sebelum dan sesudah intervensi pada kedua kelompok dilakukan pengukuran pengetahuan dan sikap menggunakan kuesioner. Uji perbedaan pengetahuan dan sikap di antara kedua kelompok dilakukan dengan uji t. Hasil analisis perbedaan antara fase sebelum dan sesudah perlakuan, menunjukkan nilai p = 0,000, baik untuk kelompok dengan intervensi ceramah maupun pemutaran film. Namun, perubahan pengetahuan dan sikap lebih menonjol pada kelompok dengan media film. Disimpulkan bahwa media pemutaran film lebih efektif untuk meningkatkan pengetahuan dan sikap kader posyandu tentang kusta.Kata kunci: kusta; kader kesehatan; pengetahuan; sikap; pemutaran film